(untitled) (Clinics, 2007)
OBJECTIVE: To test an intra-articular reconstruction of the anterior cruciate ligament of the knee in 10 human cadavers by replacing 2 anterior cruciate ligament bundles, with the purpose of producing a surrogate that would be structurally more similar to the anatomy of the anterior cruciate ligament and would provide the knee with more stability. METHODS: We reconstructed the anteromedial and posterolateral bundles using a quadriceps muscle tendon graft that included a patellar bone segment. The anteromedial bundle was replaced in 10 knees (5 right and 5 left knees from different cadavers) by a quadriceps-bone tendon graft, and the anteromedial and posterolateral bundles were replaced in the matching pairs of these knees. In the latter, the bone segment was fixed to the tibia, and the tendinous portion of the graft was divided longitudinally creating two 5-mm wide bundles that were inserted individually into the femur through 2 independent bone tunnels. Then, the knees were tested mechanically to evaluate the tibial anterior dislocation in relation to the femur, as well as the rigidity of the graft. The control group was formed by the knees with intact anterior cruciate ligaments, before being resected to be reconstructed. RESULTS: The results obtained did not show superiority of double-bundle reconstruction over single-bundle reconstruction, and neither technique provided the knee with the same stability and rigidity of the intact anterior cruciate ligament. CONCLUSION: Our hypothesis, based on the anatomy and biomechanics of the knee, that reconstruction of the anterior cruciate ligament using 2 bundles would result in a more anatomic reconstruction and provide better containment of the anterior tibial translation was not supported by the results of this study.